2-Bromopyridine-3-carboxylic acid - Howie, R.A.; Goncalves, R.S.; de Souza, M.V.N.; Tiekink, E.R.T.; Wardell, J.L. (International Union of Crystallography, 2010)
The carboxylic acid residue in the title compound, C(6)H(4)BrNO(2), is twisted out of the plane of the other atoms, as indicated by the (Br)C-C-C-O(carbonyl) torsion angle of -20.1 (9)degrees. In the crystal, supramolecular chains mediated by O-H center dot center dot center dot N hydrogen bonds are formed with base vector [201] and C-H center dot center dot center dot O interactions reinforce the packing.